2005
DOI: 10.1039/b508855k
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of (2S,3S,4R,5S)-5-methylpyrrolidine-3,4-diol derivatives that are highly selective α-l-fucosidase inhibitors

Abstract: N-Phenylaminomethyl benzimidazolyl moieties attached at C-2 of (2S,3S,4R,5S)-5-methylpyrrolidine-3,4-diol increase the potency and selectivity of the inhibitory activity of these systems towards alpha-L-fucosidases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…[43,44] The activity of compound 6, not previously reported to the best of our knowledge, is amongst the highest reported for pyrrolidine and piperidine type iminosugars. [45][46][47][48][49] Other pyrrolidine derivatives with similar stereochemistry (i.e., 3S,4R,5S) have also been reported as strong inhibitors of al-fucosidase, [50][51][52] while some diastereomerically related isomers of 5 and 6 have shown much lower activities (e.g. K i = 165 mm for the 2R,3R,4R,5R isomer [46] ), suggesting a strong stereochemical demand of the a-l-fucosidase active site.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[43,44] The activity of compound 6, not previously reported to the best of our knowledge, is amongst the highest reported for pyrrolidine and piperidine type iminosugars. [45][46][47][48][49] Other pyrrolidine derivatives with similar stereochemistry (i.e., 3S,4R,5S) have also been reported as strong inhibitors of al-fucosidase, [50][51][52] while some diastereomerically related isomers of 5 and 6 have shown much lower activities (e.g. K i = 165 mm for the 2R,3R,4R,5R isomer [46] ), suggesting a strong stereochemical demand of the a-l-fucosidase active site.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[6][7][8][9] We have shown that the presence of an additional aromatic or heteroaromatic binding component close to the five membered iminocyclitol increases notably their inhibitory activity (1 10 vs. 2, 8 Fig. 1).…”
mentioning
confidence: 99%
“…During the synthesis of the pyrrolidine antibiotic (+)-anisomycin, Rao and co-workers used an intramolecular displacement of a mesylate with a Cbz protected amine. [49] Eustache and co-workers also relied on the introduction of a mesylate and subsequent intramolecular displacement by a protected amine during the synthesis of an arabinofuranosyltransferase inhibitor, [50] while, en route to the synthesis of aminopyrrolidinediols, Robina and coworkers [51] introduced a mesylate group then an azide whose subsequent reduction led to intramolecular cyclisation. Similar azide/reduction methodology was used by Clinch et al when preparing the enantiomer of the azanucleoside immucillin H. [52] Here, protected lyxonolactone 82 was reduced to diol 83, di-mesylated to provide 84, then mono-substituted (Ǟ 85).…”
Section: Substitution Reactionsmentioning
confidence: 98%